Identification of Students' Conceptual Understanding of Momentum Material in Class X MIPA 1 SMA Adhyaksa 1 Jambi - Diki Chen; Corry Carolina Simanjuntak; Rizki Alfiana (Cahaya Ilmu Cendekia Publisher, 2022)
Research objectives: This study aims to identify the level of understanding of the class X Mipa 1 SMA Adhyaksa regarding the material momentum. Methodology: The type of research used is a quantitative research method used in this research, namely descriptive quantitative. The population of this research is 30 high school students. Main findings: Based on the results of the study, it was found that the level of students' understanding of the momentum material was relatively low, namely <59.18, whereas for each sub-material, the level of understanding was also relatively low. The average value for the momentum sub-matter is 61.111, the impulse is 58.5720, and the collision is 59.5237. This reasonably common understanding will undoubtedly have an impact on student learning outcomes. This level of knowledge will, of course, change over time according to the circumstances of the students. For this reason, the teacher's role is needed in guiding students to lead to better changes. Novelty/Originality of this study: This research aims to find out how the level of understanding of the concept, especially the material momentum and impulse.